Faktor Maternal, Keragaman Pangan dan Kelengkapan Imunisasi sebagai Determinan Stunting Baduta di Kecamatan Kalinyamatan Kabupaten Jepara: The Maternal, Dietary Diversity, and Immunization Completeness Factors as the Determinants of Two-Year-Old Toddler Stunting in Kalinyamatan District Jepara Regency - Hayuningsih, Akmaliya; Kartasurya, Martha Irene; Suhartono, Suhartono; Sutiningsih, Dwi; Adi, Mateus Sakundarno (Universitas Airlangga, 2024)
Background: Stunting affects the quality of a country's human resources so it is important to prevent and overcome it. Stunting cases in Kalinyamatan Jepara District have increased from 12.4% in 2021 to 18.9% in 2022 and to 19.05% in 2023. Objectives: This research analyzed the stunting risk factors of two-year-old toddlers in Kalinyamatan district, Jepara Regency. Methods: This case-control study involved 77 stunting children and 77 normal children. The researchers selected the subjects at the integrated health care service with the highest number of visitors of two-year-old toddlers from 12 villages in Kalinyamatan district, Jepara regency, based on the inclusion and exclusion criteria. The research lasted from March to April 2024. The researchers collected the primary data with a questionnaire and the dietary diversity with a food recall questionnaire for 2x24 hours. Secondary data was collected from the mother-child health book (KIA). Results: The results showed no differences in terms of ages and sex types from both stunting and normal children. The multivariate analysis with logistic regression test found a correlation between the anemia history during pregnancy (OR:2.75; 95% CI:1.31 – 5.78; p:0.007), career woman status (OR: 2.81; 95% CI: 1.24-6.37; p:0.014), low birth weight (OR: 3.98; 95% CI: 1.54-10.27; p:0.004), low dietary diversity (OR: 3.71; 95% CI: 1.63-8.44; p:0.002), and incomplete immunization (OR: 4.02; 95% CI: 1.66-9.74; p:0.002) with the stunting prevalence. Conclusions: Maternal (the anemia history during the pregnancy, career woman status, and low birth weight), lack of dietary diversity, and incomplete immunization become the simultaneous determinants of stunting risk factors for two-year-old toddlers in Kalinyamatan district, Jepara Regency.